10 Roles of Father and Mother in Children's Rights a Psychological Perspective - Ipul Syaifullah (International Journal of Nusantara Islam, 2021)
The family is the smallest social unit in society. Although it is the smallest social unit of society, the role of the family, especially parents, is very important. In the modern era like today, for example, there are many phenomena regarding family problems in shaping the character of children. Parents' responsibility for children's education can be done by establishing cooperation in order to form children who have good character and personality in accordance with expectations. The purpose of writing this article is to explain clearly who has the full role and responsibility for the education of children in the family and explain the importance of educating and raising children through good cooperation. The method used in this paper uses qualitative methods with analytical and psychological descriptive approaches. This method is centered by reviewing some literature from several recognized sources that are relevant to the field being written. The results of this study through several sources revealed that fathers have roles and responsibilities for their children, so that the roles and responsibilities of fathers are the same as the role of mothers in nurturing and educating children in order to form children with good character and personality. The results of the second analysis show that the cooperation of fathers and mothers in caring for and educating children is very important and plays a large role in achieving goals. The higher the demands or expectations of parents on children, the higher the need for cooperation.